Novidades e transições sociotécnicas em torno do leite orgânico: um estudo na região extremo oeste de Santa Catarina - Lovatel, Marlise (2018)
The general objective of this study was to analyze the production, markets and organizational forms around organic milk, to discover and analyze how the novelties are built by family farmers and other social actors. Verifying the historical conditions that developed the organic production system in the Extreme West Region of Santa Catarina in the context of family agriculture, also identifying the socio-technical transitions generated in this system. Markets accessed by households, with the contribution of other regional social actors, were identified and analyzed in the construction of marketing channels by short chains. In order to verify the context of the agri-food system, the social organization relationships built by the multi-institutional network of organic milk were also analyzed, identifying their main actions and incentives. To achieve these objectives, two theoretical approaches were used: Norman Long's POA and the Multi-Level and Coevolutionary Perspective (PMN), in which actors act in a multidimensional manner through their agency capacity, generating novelties of different types and results. The methodology was qualitative, with primary and secondary data collection through the application of semistructured interviews in nine families of organic and transitional farmers, and eight technicians who had connections with organic milk. The research was developed in the Far West Region of Santa Catarina, specifically in nine municipalities. The main results that the research indicates is that farmers who produce organic milk and other foods develop novelties in techniques, processes and sustainability. Through their knowledge they make modifications and create new products, ways to manage the agroecosystem and increase their activities and practices. They also generate new features when accessing new short marketing channels, approaching consumers and other social actors. These innovative actions also mobilized several regional institutions for the development of organic milk. However, this novelty is still at the level of the socio-technical niche, only modifying in small degrees the socio-technical agri-food regime in force, requiring more attention and mobilization of regional actors for its consolidation, mainly in the market issues to enable and expand the commercialization of milk organic and its derivatives, processed with the organic quality, as well as so that more families can adhere to the process of organic production of milk.